Pengaruh Celebrity Endorser dan Keragaman Menu Terhadap Keputusan Pembelian Dadar Beredar dengan Minat Beli Sebagai Variabel Intervening: Studi Kasus Mahasiswa Fakultas Ekonomi dan Bisnis Universitas Dharma Andalas - Azahra Salsabila; Alvin Alfian (Ikatan Da'i Indonesia, 2026)
This research aims to analyze the influence of celebrity endorsers and menu variety on purchase decisions for Dadar Beredar products, incorporating purchase intention as an intervening variable. The research method employed is a quantitative explanatory approach involving 120 respondents from the Faculty of Economics and Business, Universitas Dharma Andalas, selected via purposive sampling. Data were analyzed using Structural Equation Modeling (SEM) based on Partial Least Squares (PLS). The results demonstrate that celebrity endorsers and menu variety have a positive and significant direct influence on purchase decisions. Furthermore, purchase intention is proven to significantly mediate the influence of celebrity endorsers and menu variety on student purchase decisions. An R-Square value of 0.813 indicates that the independent and mediating variables in this model account for 81.3% of the variation in purchase decisions, suggesting that the research model possesses strong predictive capabilities.